Debulking different Corona (SARS-CoV-2 delta, omicron, OC43) and Influenza (H1N1, H3N2) virus strains by plant viral trap proteins in chewing gums to decrease infection and transmission - Daniell, Henry; Nair, Smruti K.; Guan, Hancheng; Guo, Yuwei; Kulchar, Rachel J.; Torres, Marcelo D.T.; Shahed-Al-Mahmud, Md; Wakade, Geetanjali; Liu, Yo-Min; Marques, Andrew D.; Graham-Wooten, Jevon; Zhou, Wan; et al. (Biomaterials, 2022)
Because oral transmission of SARS-CoV-2 is 3–5 orders of magnitude higher than nasal transmission, we investigated debulking of oral viruses using viral trap proteins (CTB-ACE2, FRIL) expressed in plant cells, delivered through the chewing gum. In omicron nasopharyngeal (NP) samples, the microbubble count (based on N-antigen) was significantly reduced by 20 μg of FRIL (p < 0.0001) and 0.925 μg of CTB-ACE2 (p = 0.0001). Among 20 delta or omicron NP samples, 17 had virus load reduced below the detection level of spike protein in the RAPID assay, after incubation with the CTB-ACE2 gum powder. A dose-dependent 50% plaque reduction with 50–100 ng FRIL or 600–800 μg FRIL gum against Influenza strains H1N1, H3N2, and Coronavirus HCoV-OC43 was observed with both purified FRIL, lablab bean powder or gum. In electron micrographs, large/densely packed clumps of overlapping influenza particles and FRIL protein were observed. Chewing simulator studies revealed that CTB-ACE2 release was time/dose-dependent and release was linear up to 20 min chewing. Phase I/II placebo-controlled, double-blinded clinical trial (IND 154897) is in progress to evaluate viral load in saliva before or after chewing CTB-ACE2/placebo gum. Collectively, this study advances the concept of chewing gum to deliver proteins to debulk oral viruses and decrease infection/transmission. [Display omitted] Twitter headline: Chewing gum neutralizing both SARS-CoV-2 and influenza viruses is advanced to clinical testing.